THE INFLUENCE OF BRAND IMAGE AND LIFESTYLE ON PURCHASING DECISIONS IPHONE IN JAMBI CITY - Agesha Marsyaf; Dimas Ihza Rifandi; Rian Dani (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The purpose of this study is first to determine the effect of brand image on iPhone purchasing decisions. The second is to determine the effect of lifestyle on iPhone purchasing decisions. The third is to determine the effect of brand image and lifestyle on iPhone purchasing decisions. The first data analysis method used was the instrument test. Both are multiple linear regressions. The third uses hypothesis testing. The results of this study concluded that brand image and lifestyle influence iPhone purchasing decisions. Both brand image and lifestyle affect iPhone buying decisions. The three brand images and lifestyles simultaneously have a significant effect on iPhone purchasing decisions in Jambi City.